Penggunaan Arsitektur Terapeutik pada Hunian Vertikal: Studi Kasus: AMN Surabaya - Aini Maharani; Yusvika Ratri Harmunisa (Arsir: Jurnal Arsitektur, 2026)
Abstract The development of the urban population has increased significantly every year, especially in areas close to educational centers such as universities in Surabaya. Where there are scholarships that facilitate student dormitories for 2 full years from various groups, and regions throughout Indonesia, namely AMN Surabaya. The environment of the Indonesian student dormitory needs to support the comfort and mental health of its residents. However, because of cultural differences from sabang to Merauke, students are less adaptable in the Surabaya environment. Therefore, a therapeutic architectural approach is needed in the design of spaces that support psychological and physical health, so this approach is suitable for overcoming problems. This study aims to determine the extent to which the application of therapeutic architectural principles in the design of the National Student Dormitory (AMN) in Surabaya as a form of vertical housing for students. The method used in this study is a qualitative descriptive method, by collecting direct observation data and document analysis related to the principles of therapeutic architecture. This study is resulted in an exploration of the potential application of therapeutic architectural principles in the design of student housing, focusing on the case of AMN Surabaya, and contributing to the development of architectural designs that are more humanistic and responsive to the psychological needs of residents.